Translation Quality Assessment of Diaphasic Intralingual Translation: A Functionalist Approach - Hill-Madsen, Aage (TTR)

(untitled) (Association canadienne de traductologie, 2024)
This article proposes a Translation Quality Assessment (TQA) framework for a particular type of intralingual translation, namely the interregisterial transformation of specialized texts into ones suitable for a lay target readership, also known as diaphasic intralingual translation. Based on a functionalist linguistic and translation-theoretical approach, this framework is designed to assess and promote registerial adequacy in diaphasic intralingual target texts. The article associates this adequacy with maximum transparency of meaning in target texts and identifies five different principles as more specific quality criteria: (1) iconicity between meanings and wordings, (2) familiarity of lexis, (3) explicitness of meanings, (4) groundedness or concreteness, and (5) coherence. These five principles are in some cases subcategorized and in all cases defined in terms of linguistic manifestations. Examples are drawn from the lay-oriented genre known as Patient Information Leaflets, i.e., the small brochures included with medicinal products that provide information and instructions to the user. Most cases include both “positive” and “negative” examples, i.e., instances of both adherence and non-adherence to a given principle. Many of the “negative” examples are followed by suggestions for improvement.